2019
DOI: 10.1042/bsr20190720
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin modulates signaling pathways and induces apoptosis in cervical cancer cells

Abstract: Cancer cells have the unique ability to overcome natural defense mechanisms, undergo unchecked proliferation and evade apoptosis. While chemotherapeutic drugs address this, they are plagued by a long list of side effects and have a poor success rate. This has spurred researchers to identify safer bioactive compounds that possess chemopreventive and therapeutic properties. A wide range of experimental as well as epidemiological data encourage the use of dietary agents to impede or delay different stages of canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(63 citation statements)
references
References 84 publications
6
56
0
1
Order By: Relevance
“…The changes to nuclear morphology of HeLa cells treated with 10 and 20 µM for 48 h also justifies the assumption that apoptosis was induced by luteolin, as nuclear condensation, disintegration, nuclear blebbing and nuclear debris formation were visualized following luteolin treatment, while untreated cells did not show any significant changes in nuclear morphology. Several studies have reported that flavones, including luteolin, show similar nuclear morphological changes in several cancer cell lines, including HeLa, glioma, EC1 and KYSE450 cells ( 20 , 24 , 48 ).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The changes to nuclear morphology of HeLa cells treated with 10 and 20 µM for 48 h also justifies the assumption that apoptosis was induced by luteolin, as nuclear condensation, disintegration, nuclear blebbing and nuclear debris formation were visualized following luteolin treatment, while untreated cells did not show any significant changes in nuclear morphology. Several studies have reported that flavones, including luteolin, show similar nuclear morphological changes in several cancer cell lines, including HeLa, glioma, EC1 and KYSE450 cells ( 20 , 24 , 48 ).…”
Section: Discussionmentioning
confidence: 94%
“…Exposure of HeLa cells to 5, 10 and 20 µM luteolin for 48 h resulted in disintegration of the DNA in a ladder-like pattern, while intact DNA was observed in the untreated control. The degree of fragmentation increased in a dose-dependent manner when treated for 48 h. Flavonoids, including chrysin and quercetin, have also been demonstrated to fragment DNA in different cell lines ( 20 , 23 , 49 , 50 ). Cell cycle analysis revealed that luteolin induced sub-G1 arrest following treatment with 20 µm for 48 h, in agreement with previous studies, where arrest at the G2/M or G1 phase was observed when treated with luteolin in several different cell lines ( 14 , 22 , 24 , 27 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quercetin could inhibit anti-apoptotic proteins according to docking studies. Further, quercetin blocks PI3K, MAPK, and WNT pathways [79]. Genistein inhibited the growth of HeLa cells in a dose-dependent and time-dependent manner by modulating the expression of MMP-9 and TIMP-1 [80].…”
Section: Cervical Cancermentioning
confidence: 94%
“…Таким образом, данный однонуклеотидный полиморфизм, локализованный в области промоторa генa FASL, приводит к подавлению активности генов, чаще всего путем блокирования транскрипции. Этот механизм в конечном итоге приводит к развитию РШМ [55]. Модуляция экспрессии генов FAS и FASL играет важную роль в контроле апоптоза и канцерогенезе [56].…”
Section: рецепторы / Receptorsunclassified